Residential Mortgage Backed Securitization:The Market Oriented Alternative for Funding Housing in India - Jaishankar, P. R. (Indian Journal of Marketing, 2009)
The housing sector in India has assumed importance in recent years on account of investment demand and housing shortage in the country. While there has been significant improvement in housing situation, the housing shortage has been estimated at 22.40 million and the capacity of the institutional sources to meet the demand is limited. With the advent of financial sector reforms, the capital market has emerged as the central source of funds for sectoral economies. In this context, the need for tapping capital markets through securitization, assumes critical significance. Securitization is a tested market oriented resource raising mechanism with enormous potential to integrate sectoral markets with the capital market. As an off-balance sheet financing technique, it has the capacity to enhance the ability of banking sector for not only channelising long term funds to housing sector but also in increasing competitive strengths in terms of improved efficiencies in both resource raising and deployment. The development of secondary mortgage markets is linked to the development of the housing finance system in particular and the overall economy in general. It is therefore important to take into account the systemic and sectoral factors having an impact on the mortgage activities. While the development of the secondary market for mortgages will in turn be largely determined by the appetite and capacity of the market for such instruments, a strategy to develop and systematically promote residential mortgage backed securities (RMBS) on the lines of those operating in the developed nations is now critically important for India.